Conhecimento e prática de puérperas sobre o aleitamento materno - Silva, Nayana Priscilla Nascimento da (2023)
OBJECTIVE: To describe the knowledge and practice of breastfeeding among puerperal women hospitalized in the rooming-in unit of a reference maternity hospital in the state of Bahia. METHODOLOGY: This was a quantitative, descriptive study carried out with 90 puerperal women who were or were not breastfeeding. Data collection took place between August 14 and September 30, 2023, with the application of a form for women at the bedside and the collection of information obtained from medical records. The SPSS for Windows version 22.0 statistical package was used to analyze the data, describing the variables using their simple and relative frequencies. RESULTS: Among the puerperal women surveyed, 98.9% reported having had prenatal care and of these, 56.2% said they had not received any information about breastfeeding during prenatal care, 58.8% reported having been able to breastfeed within the first hour of the newborn's life, 82.2% knew the benefits of breastfeeding. With regard to knowledge about breastfeeding, 88.9% knew about the proper latching of the NB to the breast at the time of breastfeeding, 98.9% were breastfeeding their NB at the time of the interview and, of these, 68.9% were breastfeeding exclusively. 31.1% of NBs needed some kind of supplement during hospitalization, with the justification of low milk production (71.5%) being a medical indication. CONCLUSIONS: Puerperal women's knowledge and practice of the breastfeeding process are essential tools for maintaining breastfeeding, as they help to prevent difficulties during the process. Understanding the specificities related to breastfeeding can contribute to structuring and implementing strategies aimed at women and health services, in order to improve the coverage and quality of the breastfeeding process.